A descriptive study on individuals referred to the Council of Cleft Lip and Palate of Gazi University - Şadiye BACIK TIRANK; Ayse GULSEN; Belma IŞIK ASLAN; Fatma UZUNER; Neslihan ÜÇÜNCÜ; Kemal FINDIKÇIOĞLU; Hakan TUTAR; Bülent GÜNDÜZ (Gazi University, 2022)
Objective: To assess the demographic characteristics and to determine the cleft types, the characteristics of the syndrome and additional anomalies, and treatment needs of patients referred to Gazi University Faculty of Medicine Cleft Lip and Palate (CLP) Council. Materials and Method: In this retrospective study, the records of 155 individuals (97 male, 58 female) referred to the council between 2014-2018 years were evaluated. Data obtained from anamnesis, clinical forms, speech records, ear-nose-throat examination results, records of plastic surgery, and orthodontic departments were transferred into digital media. The statistical evaluation of the obtained data was done by descriptive statistical analysis and determination of the frequencies of the data. Results: It was determined that patients referred to the council were from all geographical regions and different cities of the country. The ages of the patients were between 9 days and 57 years and the mean age was 10.2 years. The individuals were mostly between 0-6 years old (40.7 %) followed by the patients between 11-18 years of age (31.6%). Families of 19 cases had a history of CLP in the last 3 generations, and there were consanguineous marriages in 29 individuals. Unilateral cleft of the soft and hard palate and primary palate (Veau III) was the most common cleft type seen in the individuals (n=71, 45.8%). The most common problems were hearing loss (n=87), language and speech disorders (n=61) heart problems (n=8) and mental retardation (n=4). The accompanying syndromes were found to be Pierre Robin sequence in 2 cases, and Van Der Woude syndrome, Goldenhar syndrome and Cruzon syndrome, each in 1 case. Conclusion: The largest number of patients referred to the council were between 0-6 years of age. It was observed that 18.7% families of the individuals had consanguineous marriage. Unilateral CLP was seen more than bilateral CLP. Individuals with CLP were found to have additional anomalies in many different regions other than the facial anomalies. The most common additional problems were hearing loss followed by language and speech disorders, and as a syndrome; Pierre Robin sequence and hemifacial microsomia.